Rosja – autorytaryzm – demokracja – między iluzją i realnością - Broda, Marian (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2014)
The prognostications and forecasts concerning Russia, the nature of the Russian state and its socio-political life are frequently characterized by the extreme or even dichotomous polarization, contradiction and volatility. The reasons and explanation for this can be sought both in the objective (the features of Russian reality) and subjective (the ways of how it is perceived, conceptualized and problematized) factors, which coexist and mutually define one another.